The Effect of Promotions and Service Quality on Customer Satisfaction Among Members of Alfamart Raya Alang-Alang Lebar - Tri Elda Rahayu; Triana Agustini; Aliming Bassi; Widarti (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This research uses explanatory research with a quantitative approach. There are three variables used in this research, namely Promotion (X1), service quality (X2), and Customer Satisfaction (Y). Data collection was obtained through distributing questionnaires to customers of Alfamart Raya Alang-Alang Lebar, Palembang city who have Member cards. The sample used in this research consisted of 100 respondents. The sampling technique used was purposive sampling. The data analysis used is descriptive analysis. The research results show that the Promotion variable (X1) has a positive and significant effect on Customer Satisfaction (Y), the service quality variable (X2) has a positive and significant effect on Customer Satisfaction (Y), the Promotion variable (X1) and the service quality variable (X2) as a whole. together they have a positive and significant effect on Customer Satisfaction (Y). Based on the results of this research, Raya Alang-Alang Lebar, Palembang city should always pay good attention to customers, and always prioritize good service so that customers are satisfied.